ANALYSIS OF PUBLIC ASSESSMENT OF THE GOVERNMENT IN OVERCOMING THE LEVEL OF CONGESTION - Anton Supartono; Sindrawati Sindrawati; Muhammad Syukrullah Abdullah (Jurnal Ekonomi, 2023)
This study aims to analyze public satisfaction with the Bandung City Transportation Service in dealing with traffic jams. This study uses a case study approach to congestion that occurs in the city of Bandung. The stages passed are plan, design, prepare, collect, analyze, and share. The results of the study show that community satisfaction at the Bandung City Transportation Service shows an unfavorable value. This is because until now there are still frequent traffic jams at locations where traffic jams often occur. It is hoped that the traffic jams that occur can be resolved soon and the wheels of the economy can run smoothly, especially in the morning and evening.